Is periodontitis a risk factor of benign or malignant colorectal tumor? A population‐based cohort study. (2nd December 2021) - Fu, Martin M.; Chien, Wu‐Chien; Chung, Chi‐Hsiang; Lee, Wei‐Cheng; Tu, Hsiao‐Pei; Fu, Earl
Abstract: Objective: To examine the risk of developing benign or malignant colorectal tumors in patients with periodontitis within 15 years using Taiwan's National Health Insurance Database. Background: Studies have shown that colorectal carcinoma often develops under inflammatory conditions and changes of microbiota in the gut. Recently, a link between Fusobacterium nucleatum, a periodontal pathogen, and colorectal carcinoma has been proposed. However, whether periodontitis is a risk of developing colorectal tumor remains uncertain. Methods: In total, 35 124 participants were enrolled from 2000 to 2015 to examine the development risk of benign colorectal tumors, including 11 708 patients with periodontitis who received therapy (group 1), 11 708 patients with periodontitis not receiving periodontal treatment (group 2), and 11 708 non‐periodontitis controls after matching for gender, age, and index year. To examine the risk of developing colorectal malignancy, 11 720 participants were assigned to each of the three groups. Cox proportional hazards model and Kaplan–Meier methods were used to compare the risks. Sensitivity analysis was performed, excluding the diagnoses during the first 1 or 5 years. Results: After the follow‐up, 177, 154, and 63 participants in group 1, group 2, and control group had benign colorectal tumors. Patients with periodontitis tended to be associated with a greater rate of having a benign colorectal tumor. The adjusted hazard ratios (aHRs) were 3.77 (95% confidence interval [CI] 2.01–4.82, p < .001) and 2.85 (95% CI 1.62–3.74, p < .001) for groups 1 and 2, respectively. Regarding the risk of malignant colorectal tumor, 20, 18, and 14 participants who developed malignant tumors were included in group 1, group 2, and control group; however, no significant increase in malignancy was observed in periodontitis groups (aHR1.92, 95% CI 0.74–2.36, p = .482; aHR 1.50, 95% CI 0.68–1.97, p = .529, for the two periodontitis groups, respectively). Conclusions: The results of this study suggest that patients with periodontitis may have an increased risk of developing benign, but not malignant, colorectal tumors.